Field reports, James L. Fuller, fall 1990 - Fuller, James L.et al (1990)
Field reports submitted by James L. Fuller for all of Iowa for fall 1990 with handwritten annotations. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed